ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¬Ù…Ù„Ø© Ø§Ù„Ø§Ø³Ù…ÙŠØ© ÙÙŠ ÙƒØªØ§Ø¨ Ø§Ù„Ø£Ø®Ù„Ø§Ù‚ Ù„Ù„Ø¨Ù†ÙŠÙ† Ø§Ù„Ø¬Ø²Ø¡ Ø§Ù„Ø£ÙˆÙ„ Ø§Ù„Ø°ÙŠ Ø£Ù„ÙÙ‡ Ø¹Ù…Ø± Ø¨Ù† Ø£ØÙ…Ø¯ Ø¨Ø§Ø±Ø¬Ø§Ø¡ - Handriawan, Doni; Hairi, Hamam (Universitas Ahmad Dahlan)
One of the fundamental rules in composing Arabic sentences is the tarkib jumlah ismiyah structure. This research aims to analyze types and patterns of jumlah ismiyah structure used in kitab